2009
DOI: 10.1038/ni.1791
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 acts on regulatory T cells to maintain expression of the transcription factor Foxp3 and suppressive function in mice with colitis

Abstract: Regulatory T cells (T reg cells) that express the transcription factor Foxp3 suppress the activity of other cells. Here we show that interleukin 10 (IL-10) produced by CD11b + myeloid cells in recombination-activating gene 1-deficient (Rag1 −/− ) recipient mice was needed to prevent the colitis induced by transferred CD4 + CD45RB hi T cells. In Il10 −/− Rag1 −/− mice, T reg cells failed to maintain Foxp3 expression and regulatory activity. The loss of Foxp3 expression occurred only in recipients with colitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
611
7
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(649 citation statements)
references
References 36 publications
(32 reference statements)
22
611
7
9
Order By: Relevance
“…These symptoms were not observed in any of the wild-type BMT mice. These observations are consistent with several previous studies that implicate IL-10 production by lymphoid or myeloid cells in the prevention of inflammation of the large intestine and, ultimately, the development of colitis [48][49][50]. Given that these mice (7/18 Il10-KO BMT mice) displayed a variety of colitis-like symptoms and did not increase their fat mass during the 12 week high-fat-diet period, we excluded these mice from the study.…”
Section: Discussionsupporting
confidence: 73%
“…These symptoms were not observed in any of the wild-type BMT mice. These observations are consistent with several previous studies that implicate IL-10 production by lymphoid or myeloid cells in the prevention of inflammation of the large intestine and, ultimately, the development of colitis [48][49][50]. Given that these mice (7/18 Il10-KO BMT mice) displayed a variety of colitis-like symptoms and did not increase their fat mass during the 12 week high-fat-diet period, we excluded these mice from the study.…”
Section: Discussionsupporting
confidence: 73%
“…24 However, there are controversial results since Chaudhry and coworkers did not detect any differences in Foxp3 expression by IL-10R-deficient Foxp3 + Tregs. 25 Moreover, it is postulated that IL-10 released by Tregs acts in an autocrine manner in order to self-regulate and expand Tregs themselves.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, it is postulated that IL-10 released by Tregs acts in an autocrine manner in order to self-regulate and expand Tregs themselves. 18,23,24,26 Therefore, to exclude any influence of IL-10 deficiency with respect to Foxp3 stability, we determined the number of Foxp3 + Tregs in the inflamed kidney by immunohistochemistry. Of note, the numbers of renal Tregs were similar both in nephritic intact expression of Foxp3 in Tregs lacking IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…27 Former FOXP3 1 T cells (exFOXP3 1 T cells), were also found particularly increased in inflamed gut-associated tissues. [27][28][29] Bluestone and colleagues performed a fate mapping study with Foxp3-GFP-Cre BAC transgenic mice to trace the stability of FOXP3 1 T cells and found that 10%-20% of FOXP3 1 Treg cells lose FOXP3 expression and exhibit inflammatory Th cell phenotypes with the ability to secrete IFN-c and IL-17. 30 On the molecular level, we have identified how the stress-activated Stub1-Hsp70 complex plays a critical role in the degradation of FOXP3 and promotion of Treg cell conversion into Th1-like cells.…”
Section: Heterogeneity Of Treg Cellsmentioning
confidence: 99%